Ergogenic and metabolites analyses of piyarom date (Phoenix dactylifera L.) using NMR-based metabolomics and its effect on Sprague dawley rats - Shanan, Hana Kadum (2018)
People with fatigue need to enhance their energy production and reduce oxidative stress-associated fatigue. In this study, ergogenic activity of different varieties of date (Phoenix dactylifera L.) was evaluated using both in vitro and in vivo study. Selection of the best date variety was based on the ergogenic attributes by antioxidant activity and chemical compositions. The bioactivity of the date fruits (Ajwa, Anbara, Rabbi, Piyarom and Deglet Nour) were evaluated by antioxidant assays, while proton nuclear magnetic resonance 1H-NMR was used to profile the metabolites of the dates. Ergogenic properties of the date was evaluated in vivo, using Sprague dawley rat model. Piyarom extract showed the highest total phenolics content (355 mg GAE/g DW), total flavonoids content (57.07 mg/100g DW), scavenging activity (IC50 of 16.2 μg/mL), ferric reducing antioxidant power (26.38 Mm Fe (II)/g), and strong antioxidant capacity (IC50 11.3 μg/mL). All the dates have high sugar content that is consistent with their ergogenic attributes electrolyte content of dates (potassium, sodium, magnesium, and calcium) were present in all the dates in substantial amounts. The principal component analysis (PCA) and partial least square discriminate analysis (PLS-DA) plots of different date varieties exhibited clear and distinct separations between the dates. The metabolites identified which may have contributed to the separation were sucrose, betaine, ascorbic acid, fructose, glycine, and arginine. The ergogenic effect of Piyarom extract was then evaluated on fatigue rats. Results of in vivo study showed that rats treated with 500 mg/kg BW Piyarom date extract demonstrated the longest endurance capacity of 10 min, that is significantly higher than that of caffeine-treated rats, as measured by forced swimming test. The rats were also found to have normal blood glucose and lactate level after treatment and the values were 5.83 ± 0.64 mmol/L, 10.75 ± 0.89 mmol/L respectively. In addition, serum LDH and creatinine kinase activity (muscle injury indicators) were found to be low 297 ± 29.21 U/L, 749.17 ± 139.40 U/L respectively, in the rats treated with the high dose date extract, suggesting that energy metabolism was more effective in these rats. In NMR-based on metabolomics data, OPLS-DA showed clear distinct separation between treated and fatigue group’s treatment. Furthermore, the OPLS-DA plots showed that metabolites of the rats fed of high dose of date extract were very similar to that of normal rats, which was not obvious in rats treated with the low dose of the extract or that of caffeine. Based on the metabolite identify a clear understanding regarding the underlying mechanism of ergogenic effect of Piyarom date fruit can be elucidation. In conclusion, improvements were seen in rats treated with high dose Piyarom date extract in terms of endurance capacity, energy metabolism, muscle injury parameters and metabolites generated that are not seen in the rats treated with caffeine. Date fruit can thus be used as an ingredient in the development of functional foods (drinks or snacks) with ergogenic property. The product will be exceptionally useful for fatigue and normal individuals who desire a more active and healthier lifestyle without the oxidative stress associated lethargy.